السوق العربية المشتركة في عصر العولمة لماذا تجددت الدعوة لإحيائها ؟ - محمود, يوسف; نيوف, ممدوح (Latakia University Journal - Economic and Legal Sciences Series, 2019)
ظل مشروع السوق العربية المشتركة حبيس الوثائق الرسمية العربية؛ ومحاولة إخراجه إلى حيز الوجود باتت هاجسا يراود الطامحين إلى رؤية أي مظهر من مظاهر التوحد العربي والى أن نكون فاعلين في منظومة الاقتصاد العالمي الجديدة. يتناول هذا البحث الظروف التي قادت إلى الدعوة لإحياء اتفاقات السوق العربية المشتركة التي وقعت في عام 1964، هذه الظروف تتعلق بعوامل محلية وعوامل دولية. 1. على الصعيد المحلي: مجموعة العوامل التي تتعلق بالأداء الاقتصادي العام في الدول العربية ونذكر منها على سبيل المثال فشل البرامج التنموية وبرامج التصنيع في تحقيق التنمية الاقتصادية، وجود الاختلالات البنيوية الكبيرة في الاقتصاد، التوزيع وإعادة التوزيع غير العادل لمدخلات ومخرجات التنمية، انكشاف الاقتصاد العربي بدرجة كبيرة نحو الخارج، التبادل اللامتكافئ بين الدول المتقدمة والدول العربية كما يتناول البحث الخلفية الاقتصادية للانكشاف الاقتصادي حيث أنها تتعلق بأسباب متعددة . 2. على الصعيد العالمي: مجموعة العوامل التي تتعلق بالأداء الاقتصادي العالمي ونقصد هنا منظمة التجارة العالمية؛ في 15/4/1994 وقع ممثلو 109 دول في مركز المؤتمرات بالمغرب اكبر اتفاق عالمي للتجارة، وقد نتج عن هذا الاتفاق اتفاقات متعددة هي: اتفاق الزراعة وبروتوكول النفاذ إلى الأسواق العالمية واتفاق المنسوجات والملابس واتفاق إجراءات الاستثمار المرتبطة بالتجارة، لذلك يتناول البحث موقف الدول العربية من الانضمام إلى الغات ومنظمة التجارة العالمية وآثار المنظمة على الاقتصاديات العربية : لابد من الإشارة إلى أن جوهر اتفاقات أورغواي يستند إلى مبدأ المنافسة الحرة القائمة على المزايا النسبية والموارد الاقتصادية للدول الأعضاء سوف تحسم مقدار المكاسب التي يمكن أن يحققها البلد العضو ، والدول العربية تعتبر دول نامية وقدراتها الاقتصادية منفردة تعتبر محدودة . يتناول البحث آثار المنظومة من خلال المحاور الرئيسية التالية: تحرير تجارة السلع الزراعية – تحرير تجارة السلع المصنعة تحرير تجارة المنسوجات والملابس. نختم البحث بالتوصيات المناسبة. The Arab joint market has so far remained on paper, and the attempt to bring it to life has been the obsession of people aspiring to see an aspect of Arab unity realized, and to see Arabs as active participants in the new international economic order. This study deals with the conditions that have led to the call for revitalization of the Arab joint market agreements signed in 1964. These conditions relate to both regional and international factors. Regionally: The regional factors are connected with the general economic performance of Arab countries, of which failure of development and industrialization plans to achieve economic development; existence of big structural imbalances of the economy; unfair distribution and redistribution of revenues; the Arab economy's high degree of exposure to outside influence; and the unbalanced exchange between Arab countries and advanced countries are but a few examples. Moreover, the study deals with the economic background of the Arab economy's exposure to outside influence. Internationally: The international factors are connected with the international economic performance, by which we mean The World Trade Organization, signed in Morocco on 15/04/1994 by representatives of 109 countries. That signing was followed by a number of accords, including a pact on agriculture, a protocol of access to international market, an agreement on textiles and clothes, and an agreement on investment procedures related to world trade. Therefore, the study explains the attitude of Arab countries towards joining the GATT, World Trade Organization as well as the effects of that organization on Arab economies. Here, it is necessary to indicate that the Uruguay accords depend on the principle of free competition, which means that the member countries' benefits are relative to their economic resources. Arab countries are developing countries and their economic capabilities are limited. The study addresses the effects of the organization on the following major tracks: liberalization of trade in agricultural products, liberalization of trade in manufactured goods, liberalization of trade in textiles and clothes. Finally, the study provides appropriate recommendations.